Strategi Alternatif Marketing Perbankan dan Lembaga Keuangan Syariah - Rizal, Sofyan (Faculty of Shariah and Law, 2012)
MUIs fatwa about illegitimating of banking interest can be seen as an opportunity of Islamic banking and Islamic financial institutions to educate the public about the importance of operations in the Islamic financial institution. This fatwa also marked that the emergency to receive interset in Islamic law has ended. Various alternative approaches in marketing can be done to work on segments of banking and Islamic financial institutions even in the middle of banking competitions. Alternative marketing approach that focuses on segment, marketing radical, and value creation, and spiritual advocate creation become very effective to face the competition of banking today. These are can be used in maintaining and even expanding the market share of Islamic bankingDOI: 10.15408/aiq.v4i1.2082